Summary of the Electrical Properties of a MOS Device on Various Semiconductors - Chanana, Ravi Kumar (European Journal of Applied Sciences, 2025)
This is a review cum research communication in brief. A summary of the electrical properties of a metal-oxide-semiconductor (MOS) device on various semiconductors of Silicon, Silicon Carbide and Gallium Nitride is presented in the form of Table 1. The electrical properties for most of the devices in the summary have been published elsewhere and this brief mainly summarizes them so as to be able to compare the properties with one below the other in one view.